2020
DOI: 10.1177/0018720820902576
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Experience From Cue Utilization in Radiological Assessments

Abstract: Objective This research was designed to examine the contribution of self-reported experience and cue utilization to diagnostic accuracy in the context of radiology. Background Within radiology, it is unclear how task-related experience contributes to the acquisition of associations between features with events in memory, or cues, and how they contribute to diagnostic performance. Method Data were collected from 18 trainees and 41 radiologists. The participants completed a radiology edition of the established c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…There were no correlations evident between self‐reported experience and any of the performance measures. This is consistent with previous work in the medical imaging domain (e.g., Carrigan et al, 2020b; Crane et al, 2018; Sunday et al, 2018; Williams et al, 2021; Williams & Drew, 2019), where self‐reported experience was unrelated to expert performance. One of the limitations associated with our study was that the performance measure included a narrow range of cardiac pathology which may mean that some echocardiographers may have more expertise with different pathologies.…”
Section: Discussionsupporting
confidence: 91%
“…There were no correlations evident between self‐reported experience and any of the performance measures. This is consistent with previous work in the medical imaging domain (e.g., Carrigan et al, 2020b; Crane et al, 2018; Sunday et al, 2018; Williams et al, 2021; Williams & Drew, 2019), where self‐reported experience was unrelated to expert performance. One of the limitations associated with our study was that the performance measure included a narrow range of cardiac pathology which may mean that some echocardiographers may have more expertise with different pathologies.…”
Section: Discussionsupporting
confidence: 91%
“…The next phase will examine whether there is a relationship between cue utilization and performance on a domain specific task. Research in the radiological medical domain has shown that cue utilization differentiates performance on a static, medical image categorization task (Carrigan et al, 2020). For the echocardiographers, who view dynamic stimuli in practice, the stimuli will include the presentation of brief movies in an independent task, to emulate their real‐world diagnostic experience.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior associated with higher cue utilization has been associated with greater performance across a range of tasks, including radiology (Carrigan et al, 2020), paediatric intensive care (Loveday et al, 2013b), audiology (Watkinson, Bristow, Auton, McMahon, & Wiggins, 2018), and anesthesiology (Crane et al, 2018). However, it is also clear that cue utilization in one context can impact performance in another, related context.…”
mentioning
confidence: 99%
“…For example, a physician might associate emphysema (feature) with poor oxygen saturation (event) and order supplementary oxygen as a precaution. The greater the application of these cue‐based associations or productions, the greater the residual resources that are made available in working memory (Brouwers, Wiggins, Helton, et al, 2016; Brouwers, Wiggins, Griffin, et al, 2017; Carrigan et al, 2020).…”
Section: Cue Utilisationmentioning
confidence: 99%
“…The greater the application of these cue-based associations or productions, the greater the residual resources that are made available in working memory (Brouwers, Wiggins, Helton, et al, 2016;Brouwers, Wiggins, Griffin, et al, 2017;Carrigan et al, 2020).…”
Section: Cue Utilisationmentioning
confidence: 99%